2007
DOI: 10.1084/jem.20061943
|View full text |Cite
|
Sign up to set email alerts
|

Dietary copper supplementation reverses hypertrophic cardiomyopathy induced by chronic pressure overload in mice

Abstract: Sustained pressure overload causes cardiac hypertrophy and the transition to heart failure. We show here that dietary supplementation with physiologically relevant levels of copper (Cu) reverses preestablished hypertrophic cardiomyopathy caused by pressure overload induced by ascending aortic constriction in a mouse model. The reversal occurs in the continued presence of pressure overload. Sustained pressure overload leads to decreases in cardiac Cu and vascular endothelial growth factor (VEGF) levels along wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
172
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 158 publications
(188 citation statements)
references
References 30 publications
7
172
1
Order By: Relevance
“…Previous studies in vivo have shown that dietary Cu supplementation-induced regression of hypertrophic cardiomyopathy was partially mediated by VEGF-dependent angiogenesis [1]. To determine the role of VEGF in the direct effect of Cu on cardiomyocyte hypertrophy, an anti-VEGF antibody at a final concentration of 2 ng/ml was added before the addition of 5 μM Cu element in the PE-treated cultures.…”
Section: Cu-induced Reduction In Cell Size Was Vegf-dependentmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies in vivo have shown that dietary Cu supplementation-induced regression of hypertrophic cardiomyopathy was partially mediated by VEGF-dependent angiogenesis [1]. To determine the role of VEGF in the direct effect of Cu on cardiomyocyte hypertrophy, an anti-VEGF antibody at a final concentration of 2 ng/ml was added before the addition of 5 μM Cu element in the PE-treated cultures.…”
Section: Cu-induced Reduction In Cell Size Was Vegf-dependentmentioning
confidence: 99%
“…Previous studies have shown that dietary supplementation with physiologically relevant levels of copper (Cu) reversed pressure overload-induced cardiac hypertrophy in a mouse model along with a complete recovery of the contractile function of the heart [1]. Although the regression of cardiac hypertrophy by dietary copper supplementation in humans is unknown, a recent study in a small population of chronic heart failure patients has shown that dietary supplementation with micronutrients for 9 months increased left ventricle ejection, decreased left ventricle volume, and improved the quality of life [2].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations